The Differences between Pre- and Post-Therapy Levels of Platelet Count and Platelet Indices in Children with Immune Thrombocytopenia Purpura - Kusumaningrum, Regina Rania Cahya; Andarsini, Mia Ratwita; Hernaningsih, Yetti; Romadhon, Pradana Zaky (Folia Medica Indonesiana, 2024)
Highlights: 1. This study was the first to analyze the therapeutic response in children with ITP at Dr. Soetomo General Academic Hospital, Surabaya. 2. This study analyzed the response of platelet count and indices, including MPV, PDW, P-LCR, and PCT to therapy, which provides a more comprehensive perspective on therapy response in children with ITP. 3. This study explored the effectiveness of various therapeutic approaches based on ITP categories, offering new insights into the most effective treatment options for children with ITP. Abstract Immune Thrombocytopenia Purpura (ITP) is an autoimmune disorder triggered by antiplatelet autoantibodies. Clinically, ITP is classified into three phases including Newly-Diagnosed ITP, Persistent ITP, and Chronic ITP, each with distinct durations and therapy implications. Patients with ITP who do not receive appropriate or optimal treatment are at a heightened risk of morbidity and mortality related to bleeding complications, the condition could worsen, potentially resulting in fatal consequences. In ITP patients, platelet counts decrease, accompanied by abnormal shifts in platelet indices, including Mean Platelet Volume (MPV), Platelet Distribution Width (PDW), Platelet Large Cell Ratio (P-LCR), and Plateletcrit (PCT). Thus, therapeutic response in ITP patients can be evaluated through increased platelet counts and normalization of platelet indices. This study aimed to assess the therapeutic response of platelet counts and platelet indices in pediatric ITP patients by comparing pre- and post- therapy levels overall by category, across all medication types administered, and according to the specific medication used within each category. The result of this study are expected to provide an overview of the most effective treatments across all ITP categories in order to prevent severe complications and reduce the risk of mortality. This retrospective study included ITP patients under 18 years old at Dr. Soetomo General Academic Hospital, Surabaya, conducted from September 2023 to March 2024. Platelet count and platelet indices pre- and post-therapy levels were analyzed using the Paired T-test for normally distributed data and the Wilcoxon test for non-normally distributed data, with significance set at p < 0.05. In summary, there were notable changes in the pre- and post-therapy levels of platelet, MPV, PDW, P-LCR, and PCT in each ITP category and for all therapies. Platelet count and PCT increased, while MPV, PDW, and P-LCR decreased. Patients treated with prednisone exhibited the best therapeutic response. Among the categories, Newly Diagnosed ITP demonstrated the most optimal therapeutic response. Overall, ITP therapy led to significant differences between pre- and post-therapy levels, marked by an increase in platelet counts and normalization of platelet indices.